MODERN LABORATORY DIAGNOSIS OF PREGNANT WOMEN WITH ATHEROSCLEROSIS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Atherosclerosis is a chronic condition characterized by the accumulation of lipids and other substances on arterial walls, leading to their thickening and loss of elasticity. This condition is particularly dangerous for pregnant women, as it can affect uteroplacental blood flow, increasing risks for both the mother and the fetus. The relevance of laboratory diagnostics in this patient group lies in the need for timely detection and management of atherosclerotic changes to prevent pregnancy and delivery complications.